Implementing the SDG14 in Mexico: Diagnosis and Ways Forward - Rivera Arriaga, Evelia; Azuz-Adeath, Isaac (My University, 2019)
Sustainable Development Goal 14 (SDG14) set out specific targets for countries, developed and developing, to meet within a given time frame, with achievements monitored periodically to measure progress. To achieve the global transition to sustainable development, countries are now establishing an enabling environment of policies, institutions and governance grounded in a sound evidence-based approach that takes into account the three dimensions of sustainability (economic, social and environmental) – with closely interwoven targets. Given the challenges that Mexico has to face for addressing SDG14- the country has to acknowledge the close interaction among all the SDGs among themselves, and the special conditions required as well as the implications for their implementation. This paper provides examples in each one of the relation-ships among all the SDG targets giving an assessment of the actions that Mexico is implementing to fulfil its international commitment towards the SDG14.
Costas
Keywords: Coastal and marine management; sustainable development goal 14; México